Regret Aversion Bias dan Risk Tolerance Investor Muda Jakarta dan Surabaya (Jurnal Manajemen dan Kewirausahaan, 2009)
Investment decision behavior is an interesting topic in finance research. Bailey and Kinerson’s (2005) research found that individual risk tolerance and experienced regret significantly influenced investment decisions. Anticipation of potential future regret did not predict subsequent investment decision behavior. Specifically, this research also wants to know the effects of a person’s experienced regret and anticipated regret or the effects of individual risk tolerance on investment decision behavior in Jakarta and Surabaya. Respondent of this research is 323 students from UK Petra who represent young investors from Surabaya and students from UPH who represent young investors from Jakarta. The method of research is experimental study and the design of research is 2x2x2 (between subject) with experienced regret (time deposit and stock) as first variable, anticipated regret (time deposit and stock) as second variable and risk tolerance (high and low) as third variable This study finds that an individual risk tolerance significantly influences decisions. Regret aversion bias does not influence young investors in Indonesia. (We assume that it is because the character of Indonesian investors is different from foreign investors). The couse of this is supposedly the unique characteristics of Indonesian investors and the different view points between Indonesian investors and investors from other countries.Abstract in Bahasa Indonesia:Perilaku keputusan investasi sangat menarik untuk diteliti. Dalam penelitian Bailey dan Kinerson (2005) ditemukan risk tolerance dan experienced regret mempengaruhi keputusan investasi. Anticipated regret tidak dapat dipakai sebagai predictor perilaku keputusan investasi. Penelitian ini juga ingin mengetahui experienced regret, anticipated regret atau risk tolerance yang lebih mempengaruhi perilaku keputusan investasi di Jakarta dan Surabaya. Responden yang diteliti sebesar 323 mahasiswa berasal dari UK Petra yang mewakili investor muda Surabaya dan UPH mewakili investor muda Jakarta. Penelitian akan dilakukan dengan metode eksperimental dan design penelitiannya adalah 2 x 2 x 2 (between subject) dengan variabel pertama adalah experienced regret (deposito vs. saham), variabel kedua adalah anticipated regret (deposito vs. saham), dan variabel ketiga adalah risk tolerance (rendah dan tinggi). Hanya risk tolerance yang mempengaruhi keputusan investasi para investor muda di Jakarta dan Surabaya. Regret aversion bias tidak terjadi pada perilaku investor muda di Indonesia. Hal ini diduga adanya karakter unik dan cara pandang yang berbeda investor Indonesia dengan investor negara lain. Kata kunci: risk tolerance, experienced regret, anticipated regret, investor bias